Delaware’s Fiduciary Imagination: Going-Privates and Lord Eldon’s Reprise - David Kershaw (Washington University Law Review, 2021)
What does it mean to be a fiduciary and does it really matter whether the law labels a person a fiduciary or not? Until the late twentieth century Delaware corporate law could have given a singular, coherent answer to these questions. Today, to its detriment, it is no longer able to do so. Part I of this Article explores the different conceptions of fiduciary relations. It first explores the power/undertaking conception of fiduciary relations in relation to directors and majority shareholders and shows how statements in U.S. corporate law that appear inconsistent with it—because they suggest duties are owed outside of the corporation, such as directorial duties to stockholders or majority shareholder duties to minority shareholders—are often on closer inspection not inconsistent at all. Part I then turns to the nature and “fiduciarization” of the undue influence doctrine, its importation into Delaware law, and its implications for the nature and structure of fiduciary obligation. Part II of the Article considers the application of these fiduciary conceptions to controlling shareholders, first highlighting the initial dominance in U.S. law generally, and Delaware law in particular, of the power/undertaking conception, and second, documenting the rise and impact of the influence conception in Delaware going-private law. Part III provides another example of the effects of the infusion of the fiduciary influence conception in the context of whether director’s fiduciary duties are owed directly to creditors. The Conclusion concludes.
Keywords: Fiduciary duties; Fiduciary imagination; Fiduciary influence; Going-private mergers; Corporate law; Delaware law